Pengaruh Pemberian Agar-Agar Lidah Buaya Terhadap Kejadian Keputihan - Cecilya Kustanti (Jurnal Keperawatan Notokusumo, 2016)
Background: Whitish in adolescents is often found in adolescents who are less concerned about the cleanliness and maintenance of the area genetalia.High rates of vaginal discharge in women and girls in the world and in Indonesia, as well as the impact that fatal if not addressed properly so we need a way / srategi to overcome white, one with consuming aloe vera jelly that has efficacy without side effects. Objective: To investigate the effect of Aloe Vera Jelly on the incidence of white girls. Methods: This study used a quasi-experimental methods (quasi experiment) or experimental research design using the design of treatment Time Series Design.Treatment respondents 35 people, 25 control respondents that was done in Suren Kulon village, Canden, Jetis, Bantul, Yogyakarta on stage preparation was carried out in April 2015 and the implementation of activities in June 2015 and the completion of a report in July 2015 Results: Based on the analysis of the decline in average order granting that aloe vera visible difference was statistically significant with p = 0.001 p (= 0.05) between the treatment group and the control group. A decrease in vaginal discharge that occurred in the treatment group -11.6211 of pre-test to post-test. Conclusion: Giving Aloe Vera Jelly has an influence on discharge rate reduction experienced by young women.